Region Building Complex Social and Economic Security Threats - Kozachenko, Hanna; Onychshenko, Svitlana; Masliy, Oleksandra (International Journal of Engineering and Technology, 2018)
The basic threats of region building complex social and economic security were investigated. From the standpoint of protective approach established negative factors, which provoke the appearance, threats and significantly reduce the level of region building complex social and economic security. It was found real threats to region building complex economic security. On the basis of multi-material division threats to region building complex economic security were systematized. It was underlined that the proposed division of threats can solve a set of problems in ensuring region building complex economic security.Â